Inverse association between IgG-anti-κ and antierythrocyte autoantibodies in patients with cold agglutination - Terness, Peter; Navolan, Dan Bogdan; Opelz, Gerhard; Roelcke, Dieter (Blood, 1999)
It has been known for a long time that IgG-anti-F(ab')(2) antibodies (Abs) are able to suppress the B-cell response. We showed that natural IgG-anti-F(ab')(2) autoantibodies appear in the serum of patients with cold agglutination. If the anti-F(ab')2 Ab suppresses cold agglutinin (CA)-producing B cells, one would expect an inverse correlation between the titers of these two Abs. Our study confirmed this correlation. Subsequent experiments showed that some anti-F(ab')(2) Abs bind to the hinge region of IgG. It was difficult to explain how this Ab suppresses CA-producing B cells, which are of IgM isotype. Here we show that patients with cold agglutination have an IgG-anti-kappa light chain autoantibody in their serum. This is another member of the anti-F(ab')(2) Ab group. Because the vast majority of CAs are IgM-kappa Abs, the anti-kappa Ab might suppress CA-producing B cells. If this is the case, there should be an inverse association between the titer of anti-kappa Ab and CA. In a group of 302 patients, we found that high titers of the anti-kappa Ab correlate with low titers of CA and vice versa (P =.009). Interestingly, this association is found only in patients whose disease is caused by noninfectious agents, including mainly B-cell proliferations (P =.0058). Our data show that the inverse correlation is not confined to a particular CA autoantibody specificity. The results are discussed in the light of recent findings showing that anti-IgM Abs may either inactivate or kill tumoral B cells by apoptosis.